Hierarchical Linear Modeling of the relationship between Attitudinal and Instructional Variables and Mathematics Achievement - Kwame Butakor, Paul (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Students achievement in mathematics is often considered necessary for the success of the future of a country. Therefore, the training and preparation of students to do well in mathematics has become fundamental goal of educat ion for most countries and more specifically in Ghana. Applying Hierarchical Linear Modeling on the Trends in International Mathematics and Science Study (TIMSS) 2007 data, the relationship between attitudinal and instructional variables and mathematics achievement among Ghanas grade eight students was examined. Prior to the analyses, exploratory factor analyses were conducted for clusters of similar items to reduce the number of predictor variables. The results indicate that students gender, educational aspirations, self-confidence in mathematics, value for mathematics, and frequent use of some instructional variables were significant positive predictors at Level 1. Whiles amount of homework, years of teaching, major area of study were significant positive predictors, teaching license or certificate was a significant negative predictor at Level 2.